Rola strategii rozwoju lokalnego w zarządzaniu gminą - studium przypadku gminy Lubań - Ignacy, Jarosław; Kopyściański, Tomasz (The Imoprtance of Local Development Strategy for Management Process in a Commune on the Example of Lubań, 2008)
The increasing role of a communal self-government triggers the need of introducing strategic approach in the management process. This is reflected in a recently observed increased interest of communes in working out local development strategies. It is obvious that it is only half of the success to develop a good strategy. Equally important is the implementation process and the main question is how to transform long term objectives defined in a strategy into activities undertaken by local authorities in a yearly prepared budget. Therefore the article describes current barriers and main facilitators in the proper functioning of strategy implementation process on the example of Lubań, the commune from Lower Silesia region.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 106-113